Poorly Understood Pelvic Venous Disorders Require a Multidisciplinary Approach - Doganci, Suat (Phlebologie, 2021)
Pelvic venous diseases encompasses all chronic pathologies of pelvic veins caused by venous hypertension and retrograde flow in pelvic veins. It is commonly unexplained and often underdiagnosed cause of chronic pelvic pain in women of productive age. Pelvic venous pathologies are a part of multidisciplinary problem that should be considered in a holistic approach. Newly offered SVP classification may help correctly classifying patients and using the same nomenclature. Endovascular treatment options are highly effective with good long-term results. Patients with inconclusive gynecologists examinations should be referred to a specialist for the investigation of pelvic venous disorders.
Keywords: pelvic venous disease; pelvic congestion; chronic pelvic pain